Truce thinking and just war theory. Issue 1 (2nd January 2017) - Breen, Keith
ABSTRACT: In his book, A Theory of Truces, Nir Eisikovits offers a perceptive and timely ethics of truces based on the claim that we need to reject the 'false dichotomy between the ideas of war and peace' underpinning much current thought about conflict and conflict resolution. In this article, I concur that truces and 'truce thinking' should be a focus of concern for any political theory wishing to address the realities of war. However, Eisikovits's account, to be convincing, requires engagement with a tradition of thought figuring only marginally in his reflections on truces, that is, just war theory. I argue this for three reasons. Without incorporation of the just war principles that should inform the decisions to enter conflict, to maintain conflict, and to cease conflict, any theory of truces will be, first, normatively inadequate, failing to provide us with requisite direction, and, second, open to the charge of permitting intolerable injustices, a charge Eisikovits wishes to avoid. Third, engagement with just war theory is important for arriving at a nuanced understanding of peacemaking, one which grants truces their place in our deliberations and spurns simplistic 'war versus peace' binaries whilst keeping more ambitious ideals of peace firmly in sight.